Social isolation in the young and middle-aged patients with stroke: role of social support, family resilience and hope - Wu, Xiao Jia; Ke, Ke; Liu, Hui; Zhan, Shao Ping; Wang, Lei; He, Juan Feng (Frontiers in Psychiatry, 2025)
BackgroundStroke is the leading cause of death and disability among adults in China. Social isolation in stroke survivors is a major public health concern across the globe. Social isolation is associated with social support, family resilience, and levels of personal hope, but how they interact to predict social isolation in the young and middle-aged stroke survivors remains unclear.MethodsUsing cross-sectional design and convenience sampling method, a survey was conducted among 461 young and middle-aged stroke survivors. Perceived social support scale, General isolation Scale, Chinese version of Family Resilience Assessment Scale and Herth hope index were adopted to assess patients’ social, family and personal factors. SPSS 27.0 and AMOS 26.0 were used for descriptive analysis and structural equation modeling of the data.ResultsThe young and middle-aged stroke survivors had a high level of social isolation(49.57 ± 5.84). In the mediating effects model, social support could influence social isolation directly (95% CI -0.250, -0.061) or indirectly through family resilience (95% CI -0.136, -0.062) or patient hope level (95% CI -0.078, -0.017). In addition, Family resilience and hope had a significant chain mediating effect between social support and social isolation (95% CI -0.029, -0.006).ConclusionsSocial support can have both direct and indirect effects on social isolation through the mediating factors of family resilience and hope. Clinicians and nurses can develop supportive interventions by taking integration of family and personal hope. On the one hand, resources can be directed to the individual patient, and on the other hand, the utilization of social support can be ensured by increasing family resilience and enhancing the coping capacity of family members and individuals.